Synthesis and Characterization of Iron(III) and Uranyl(II) Complexes of Some Salicyloylhydrazones - Senthil Sivakumar, B.; Manimekalai, A. (Asian Journal of Chemistry, 2010)
Iron(III) and uranyl(II) complexes of salicyloyl hydrazones derived from 2,6-diphenylpiperidin-4-one (DPSH) and 3-methyl-2,6-diphenylpiperidin- 4-one (MDPSH) were prepared and characterized by elemental analysis, conductance, magnetic, cyclic voltammetric and spectral studies. UO2(II) complexes derived from DPSH and MDPSH have 1:1 and 2:1 metal to ligand stoichiometries, respectively. The metal ligand ratio was found to be 1:3 in Fe(III)-DPSH complex and 1:2 in Fe(III)-MDPSH complex. Based on the relevant data probable structure of the complexes were proposed.